2022
DOI: 10.1029/2022gb007428
|View full text |Cite
|
Sign up to set email alerts
|

Molecular‐Multiproxy Assessment of Land‐Derived Organic Matter Degradation Over Extensive Scales of the East Siberian Arctic Shelf Seas

Abstract: Global warming triggers permafrost thaw, which increases the release of terrigenous organic matter (terr-OM) to the Arctic Ocean by coastal erosion and rivers. Terrigenous OM degradation in the Arctic Ocean contributes to greenhouse gas emissions and severe ocean acidification, yet the vulnerability of different terr-OM components is poorly resolved. Here, terr-OM degradation dynamics are studied with unprecedented spatial coverage over the World's largest shelf sea system-the East Siberian Arctic Shelf (ESAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
1
5
0
Order By: Relevance
“…Sediment δ 13 C followed previously reported trends and became less depleted further from river mouths, indicative of a shift from terrestrial to marine organic C sources (Bröder et al, 2018(Bröder et al, , 2019Martens et al, 2021Martens et al, , 2022Matsubara et al, 2022). However, we found no relationships between sediment ASi or TOC and distance from river mouths, possibly due to relatively low concentrations of both, indicative of rapid remineralization of organic material loaded on sediments in this region (Anderson et al, 2011).…”
Section: Sediment Si Accumulationsupporting
confidence: 82%
See 2 more Smart Citations
“…Sediment δ 13 C followed previously reported trends and became less depleted further from river mouths, indicative of a shift from terrestrial to marine organic C sources (Bröder et al, 2018(Bröder et al, , 2019Martens et al, 2021Martens et al, , 2022Matsubara et al, 2022). However, we found no relationships between sediment ASi or TOC and distance from river mouths, possibly due to relatively low concentrations of both, indicative of rapid remineralization of organic material loaded on sediments in this region (Anderson et al, 2011).…”
Section: Sediment Si Accumulationsupporting
confidence: 82%
“…Coastal erosion in this area is driven by the high frequency of Yedoma deposits along the coasts, that is, late‐Pleistocene permafrost deposits that are vulnerable to collapse due to their high ice content. Coastal erosion of Yedoma deposits is highest near the Buor Kaya Bay (Günther et al., 2013; Schirrmeister et al., 2017; Strauss et al., 2015), the Dmitri Laptev Strait, and the New Siberian Islands (Schirrmeister, Kunitsky, et al., 2011) and leads to significant loading of organic matter nearshore in the Laptev and East Siberian sea (Bröder et al., 2016; Matsubara et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the contribution of terrestrial organic carbon to particulate organic carbon reached 99% in the W-ESS, but accounts for as low as 1% in the E-ESS [38]. The waters of Pacific origin that also carried a labile OM fraction [38] were additionally modified on the ESS shelf owing to the interaction with the bottom sediments containing fresh autochthonous OM as well as relatively labile (compared to the western province) allochthonous OM [61]. Matsubara et al [61] showed that river-transported terrestrial OM from surface soils, which is less resistant to degradation compared to the erosion-derived terrestrial OM from ice complex deposits of the seashore and riverbank [29,30,62], prevails in the terrigenous component of the E-ESS bottom sediments.…”
Section: Spatial Dynamics Of Carbonate Parameters On the Shelfmentioning
confidence: 99%
“…The waters of Pacific origin that also carried a labile OM fraction [38] were additionally modified on the ESS shelf owing to the interaction with the bottom sediments containing fresh autochthonous OM as well as relatively labile (compared to the western province) allochthonous OM [61]. Matsubara et al [61] showed that river-transported terrestrial OM from surface soils, which is less resistant to degradation compared to the erosion-derived terrestrial OM from ice complex deposits of the seashore and riverbank [29,30,62], prevails in the terrigenous component of the E-ESS bottom sediments. For example, the degradation rate in the bottom sediments of lignin phenols coming to the shelf, mainly from seasonally melted soils, is three times as high as the degradation rate of the total sedimentary terrigenous OM pool [61].…”
Section: Spatial Dynamics Of Carbonate Parameters On the Shelfmentioning
confidence: 99%